Cultural Patterns Underlying Apprenticeship: Germany and the UK - Deissinger, Thomas [Verfasser] (My University, 2008)
"Modernisation of vocational education and training (VET) is an urgent issue in most countries. However, both structural conditions and modernisation issues differ between nations due to cultural patterns underlying VET practices. This article illustrates the firm roots of VET in the UK and Germany by looking at 'apprenticeship cultures' which seem solid, although both countries face similar challenges. Challenges and pathways to solutions appear interesting for comparative research, above all in the context of European VET policy focussing Lifelong Learning and the idea of Qualification Frameworks. Here, the two systems seem to be 'prepared' in different ways due to their respective VET traditions.
Keywords: S 1.3 Berufliche Erstausbildung; T Theorieentwicklung & Methodologie; T 1.2 Historische Berufsbildungsforschung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Berufsausbildung; Berufsbildungssystem; Berufsbildungstheorie; Historische Berufsbildungsforschung; Duales System; Beruflichkeit; Modularisierung; Kompetenzorientierung; Nationaler Qualifikationsrahmen; Europäischer Qualifikationsrahmen; Internationaler Vergleich; Vergleichende Berufsbildungsforschung; Bundesrepublik Deutschland; Vereinigtes Königreich